2020
DOI: 10.3389/fimmu.2020.02008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Candidate Epitopes on SARS-CoV-2 Proteins for South America: A Review of HLA Frequencies by Country

Abstract: tests. Additionally, the updated HLA allelic frequencies provide a better representation of South America and may impact different immunogenetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 145 publications
(198 reference statements)
1
25
0
Order By: Relevance
“…HLA-B*35 frequency in the Sri Lankan population is 21-23% [18,19]. In contrast, the most frequent HLA-A alleles in the European, US and Brazilian populations are HLA-A*0201, A*0206 (24.5 to 27.5%), which are several fold higher than in the Sri Lankan population, while HLA-A*2402 and B*3501 are lower (7.9 to 9.5%) [20][21][22]. In silico analysis, recently showed that HLA-A*0201 was associated with a higher risk of COVID-19, while HLA-A*2402 was shown to associate with higher capacity to present SARS-CoV2 antigens [23].…”
Section: Discussionmentioning
confidence: 84%
“…HLA-B*35 frequency in the Sri Lankan population is 21-23% [18,19]. In contrast, the most frequent HLA-A alleles in the European, US and Brazilian populations are HLA-A*0201, A*0206 (24.5 to 27.5%), which are several fold higher than in the Sri Lankan population, while HLA-A*2402 and B*3501 are lower (7.9 to 9.5%) [20][21][22]. In silico analysis, recently showed that HLA-A*0201 was associated with a higher risk of COVID-19, while HLA-A*2402 was shown to associate with higher capacity to present SARS-CoV2 antigens [23].…”
Section: Discussionmentioning
confidence: 84%
“…HLA-B*35 frequency in the Sri Lankan population is 21% to 23% [ 17 , 22 ]. In contrast, the most frequent HLA-A alleles in the European, US and Brazilian populations are HLA-A*0201 and A*0206 (24.5% to 27.5%), which are several fold higher than in the Sri Lankan population, while HLA-A*2402 and B*3501 are lower (7.9% to 9.5%) [ 23 , 24 , 25 ]. In silico analysis recently showed that HLA-A*0201 was associated with a higher risk of COVID-19, while HLA-A*2402 was shown to associate with higher capacity to present SARS-CoV2 antigens [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications have investigated the link between HLA variation and COVID severity using this in silico approach. Some of these studies were combined with epidemiological data (29)(30)(31) or results derived from small case control series. (32) There appears to be no clear consensus in the conclusions drawn so far.…”
Section: Discussionmentioning
confidence: 99%